Atención a los clientes del comedor nacho en la Ciudad De Babahoyo 2022. - Ramos López, Lehi Raúl (2022)
The present case is the result of a study whose purpose was to determine the level of customer satisfaction in the "Nacho Dining Room", with the aim of knowing and analyzing the factors that affect customer service, based on skills. of the employees, needs, expectations, and customer satisfaction, considering them an essential part for the company and thus be able to achieve favorable levels of sales and customer loyalty. The quality of customer service is one of the essential points that must be fulfilled within each business, in this case in the "Comedor Nacho", regardless of the size, structure or nature of its operations, they must demonstrate the capacity that they have to perform in this area, since being the first image that is given to customers helps to maintain their preference, and if it changes, it can become a threat instead of a strength. Customer service is one of the most important elements in all types of business without exception. Employees of "Comedor Nacho" are recommended to maintain a culture of customer service, since any customer who purchases a product in this place deserves to be treated in a cordial, friendly, attentive, and helpful manner. It must be clear that their strategies, actions and objectives must be completely customer oriented. It is very important that you carefully plan the tasks that involve direct contact with customers. Although many times we do not realize it, our clients are our most valuable asset.